2021
DOI: 10.1093/ibd/izaa341
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Inflammatory Bowel Diseases in Israel: A Nationwide Epi-Israeli IBD Research Nucleus Study

Abstract: Background There are currently no nationwide data on the epidemiology of inflammatory bowel diseases (IBD) in Israel. We aimed to determine the population-based epidemiological trends of IBD in the diverse Israeli population. Methods Health-administrative data were retrieved from all 4 Israeli health maintenance organizations, insuring 98% of the population, using validated identification algorithms. National trends were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…The incidence of CD and UC among Jewish Israelis was approximately twice that among Arab Israelis (CD: 16/100,000 Jewish persons; 9.6/100,000 Arab persons; UC: 11.4/100,000 Jewish persons; 6.2/100,000 Arab persons). 43 These findings suggest the role of genetic factors as major but environmental factors as a minor in IBD development.…”
Section: Inflammatory Bowel Disease In Asian Countriesmentioning
confidence: 91%
See 2 more Smart Citations
“…The incidence of CD and UC among Jewish Israelis was approximately twice that among Arab Israelis (CD: 16/100,000 Jewish persons; 9.6/100,000 Arab persons; UC: 11.4/100,000 Jewish persons; 6.2/100,000 Arab persons). 43 These findings suggest the role of genetic factors as major but environmental factors as a minor in IBD development.…”
Section: Inflammatory Bowel Disease In Asian Countriesmentioning
confidence: 91%
“…Because of the geographic differences in Southeast Asia, the incidence and prevalence of IBD vary among countries. Populationbased IBD incidence data from Indonesia, Malaysia, Singapore, and Thailand during the same period have shown that the annual 43 Nationwide study IBD incidence was less than 1/100,000 persons, which is lower than that in the West and East Asia. 16,17 During 2011-2013, the pooled annual incidence of IBD was significantly lower in Southeast Asia than in East Asia (0.8 vs. 1.53/100,000 persons; p = 0.015).…”
Section: Incidence and Prevalencementioning
confidence: 92%
See 1 more Smart Citation
“…As of 2019, 54.1% had Crohn's disease (CD) and 45.9% had ulcerative colitis (UC). 2 Optimal management of IBD relies on understanding and tailoring evidence-based interventions through shared decision-making of physicians and patients. Traditional approaches to the management of IBD care, based on treating symptoms alone and managing disease flares, have not changed the natural history of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…There is some conflicting data on the changes in prevalence of VEOIBD. On the one hand, some cohorts have reported a stable percentage of diagnosis of VEOIBD over time (10,11), and on the other hand, a relatively recent population based study (4) demonstrated that the prevalence in Canada has been increasing over the…”
mentioning
confidence: 99%